Development of 3D Printing Raw Materials from Plastic Waste. A Case Study on Recycled Polyethylene Terephthalate - Alaeddine Oussai; Zoltán Bártfai; László Kátai (Applied Sciences, 2021)
Fused Deposition Modelling (FDM) is the most common 3D printing technology. An object formed through continuous layering until completion is known as an additive process while other processes with different methods are also relevant. In this paper, mechanical properties were analysed using two distinct kinds of printed polyethylene terephthalate (PET) as tensile test specimens. The materials used consist of recycled PET and virgin PET. An assessment of all the forty test pieces of both kinds of PET was undertaken. A comparison of the test samples’ tensile strength values, difference in stress-strain curves, and elongation at break was also carried out. The reasoning behind the fracturing of test pieces that printed with different settings is presented in part by the depiction of the fractured specimens following the tensile test. An optimal route was revealed to be 3D printing with recycled PET, as per the mechanical testing. The hardness of the recycled filament decreased to 6%, while the tensile strength and shear strength increased to 14.7 and 2.8%, respectively. Nonetheless, no changes occurred to the tensile modulus elasticity. Despite notable differences being observed in the results of the recycled PET filament, no substantial differences were found prior or post-recycling in the mechanical properties of the PET filament. In conclusion, the demand for improved recycled 3D printing filament technologies is heightened due to the comparable mechanical features of the specimens of both the 3D printed recycled and virgin materials. With tensile strength figures reaching as high as 43.15MPa at Recycled PET and 3.12% being the greatest elongation at 40% Recycled PET, 100% Recycled is the ideal printing setting.